Prognostic Value of Preoperative Lymphocyte-to-Monocyte Ratio in Patients with Recurrent Colorectal Cancer - Oğuzcan Özkan; Pınar Peker; Aslı Geçgel; Erdem Göker (Medicina)
Background and Objectives: CRC is one of the leading causes of cancer-related deaths worldwide. New biomarkers are needed to identify the high-risk patient population after primary treatment and to personalize and perfect treatment and follow-up. Indicators of cancer-associated systemic inflammatory response, such as the LMR, have been widely investigated and have yielded conflicting results. The aim of this study was to investigate the effect of preoperative LMR on the prognosis of recurrent CRC. Materials and Methods: We included 204 patients admitted to our center for recurrent CRC between January 2010 and January 2015. Retrospectively, we investigated the preoperative LMR data and its effect on RFS and OS. Results: The cut-off value of LMR was 24.72 and, according to this value, we created two groups: LMR-H and LMR-L. There were 104 (50.9%) patients in the H group and 100 (49.1%) patients in the L group. The median OS was 38.0 months (95% confidence interval (CI): 30.66–45.33) for the L group and 49.0 months (95% CI: 44.06–53.94) for the H group. Overall population median OS was calculated as 44.0 months (95% CI: 40.1–47.8, p = 0.004). Median RFS was 21.3 months (95% CI: 18.3–24.2) for the LMR-L group and 28.39 months (95% CI: 24.9–31.8) for the LMR-H group (p = 0.004). Conclusions: The association between the LMR at diagnosis and early recurrence, as well as survival outcomes, was investigated in patients with recurrent CRC. Higher preoperative LMR levels were found to correlate with improved OS and RFS.